UPACARA MANGOKAL HOLI PADA MASYARAKAT BATAK DI HUTA TORUAN, KECAMATAN BANUAREA, KOTA TARUTUNG SUMATERA UTARA - Yogi Hutapea, Asfika (Humanis; Volume 11. No2. Mei 2015)
Batak traditions inherited from their ancestors in the form of ceremony Mangokal Holi, which is a hereditary tradition to honor ancestors by digging and lifting the bones of the ancestors. Through certain ceremonies bones are then placed on the monument. This tradition was inherited from generation to generation and still held to this day. This Holi Mangokal ceremony in addition to functioning as a ritual homage to the ancestors, also has a function as a social integration among families making ceremony. The use of buffalo in this ritual because it gives the impression of a magical religio buffalo has been known as a carrier animal blessing of fertility and prosperity in the society as well as a status symbol Indonesia. Kerbau people who are conducting the ceremony Mangokal Holi.
Keywords: mangokal holi, Batak, ceremony.